Measuring Tactical Behaviour Using Technological Metrics: Case Study of a Football Game. Issue 4 (December 2013) - Clemente, Filipe M.; Couceiro, Micael S.; Martins, Fernando M. L.; Mendes, Rui; Figueiredo, António J.
In football, the tactical behaviour of a team is related to the state of ball possession, i.e., the defensive and offensive phases. The aim of this study was to measure the tactical responses of two opposing teams in the moments with and without ball possession, thus trying to identify differences in results arising from tactical metrics such as weighted centroid position, weighted stretch index, surface area and effective area of play. The herein presented results show statistical differences in both teams, either with or without the ball possession, for the -axis centroid ( p-value ≤ 0.001), -axis centroid ( p-value ≤ 0.001), stretch index ( p-value ≤ 0.001), surface area ( p-value ≤ 0.001) and effective area of play ( p-value ≤ 0.001). Such results confirm that teams react depending upon ball's possession, respecting the tactical principles of width and length, as well as the unit in the offensive phase with ball possession, and also the concentration and defensive unit in the moments without ball possession.